0590 Factors Associated with Sleep Health in Young Women After Breast Cancer Treatment. (25th May 2022) - Hwang, Youri; Conley, Samantha; Jeon, Sangchoon; Redeker, Nancy; Sanft, Tara; Knobf, Mary
Abstract: Introduction: Poor sleep health adversely affects quality of life and prognosis in cancer survivors, yet there is limited evidence on sleep health in young women with breast cancer (YWBC). The purpose of this study was to identify sociodemographic, clinical, and psychosocial factors associated with sleep health. Methods: We conducted a cross-sectional study. Eligible participants were women diagnosed with stage I-III breast cancer ≤ 50 years of age and within 5 years from primary cancer treatment. Sociodemographic, clinical, and psychosocial data were collected through an online survey. Sleep health and psychosocial data were assessed by the Pittsburgh Sleep Quality Index (PSQI), PROMIS depression and anxiety, and the McMaster Family Device General Functioning subscale. Data were analyzed with logistic regression. A PSQI cut-off score of >8 was used to define poor sleep health based on the study data and the cancer sleep literature. Results: The sample included 159 YWBC with a mean age of 43.6 years (SD=6.8), the majority of whom were non-Hispanic White (84%) and completed chemotherapy or radiotherapy (>70%). Half of the participants were premenopausal at diagnosis and became peri- or postmenopausal after treatment. The mean global PSQI was 9.3 (SD=3.6) and 55% reported poor sleep health. About half of the participants slept <7 hours per night, 87% spent >15 minutes falling asleep, and 58% reported taking medication to sleep. Non-White underrepresented groups (OR=7.56, p<.01), more severe night sweats (OR=9.00, p<.001), no history of endocrine therapy (OR=2.73, p<.05), more severe anxiety (OR=1.08, p<.01) and depression (OR=1.06, p<.05), and poorer family functioning (OR=3.78, p<.001) were associated with poor sleep health. Conclusion: The findings suggest that poor sleep health is a significant clinical problem in YWBC. Sleep assessment, education, and appropriate referrals should be part of routine survivorship care. Social determinants of health such as race and ethnicity and family functioning warrant further investigation related to sleep health. Future studies are needed to confirm the relationships of sociodemographic and clinical factors, psychological symptoms, and family functioning with sleep health. Support (If Any): The Global Korean Nursing Foundation.